PERLINDUNGAN HUKUM TERHADAP USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MELALUI KERJASAMA KEMITRAAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Wa Ode, Zamrud; La Ode, Revanza Revikhasa (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2025)
The proposed research question is: What is the state of the legal regime for the protection of micro, small and medium-sized enterprises (SMEs) through partnership cooperation in the perspective of the law? What are the forms of partnership cooperation for micro, small and medium-sized enterprises (SMEs) in the perspective of Law No. 6 of 2023 on job creation? This research is part of the normative legal research typology. The research data were collected through document/library research and legal regulations, and then processed using a qualitative descriptive program. The results are presented in the form of conclusions and explanations. The analysis was carried out using a legislative and a legal approach. The results of this study showed that the legal provisions regarding the protection of SMEs are set out in laws and regulations, namely Law No. 20 of 2008 on SMEs, Law No. 6 of 2023 on Job Creation, and Government Regulation No. 7 of 2021 on Facilitating, Protecting and Strengthening Cooperatives and Micro, Small and Medium-sized Enterprises. The form of cooperation within SMEs is regulated in Law No. 6 of 2023 on Job Creation in Article 87, paragraph (5), namely the Core Plasma partnership model, subcontracting, franchising, general trade, distribution and agency, supply chain, profit sharing, operational cooperation, joint ventures and outsourcing. The form of partnership cooperation is also regulated in Article 106 of Government Regulation No. 7 of 2021. This study recommends that the form of legal protection for SMEs should be further developed, despite the fact that it is already regulated in the Employment Act and Regulation No. 7 of 2021, regarding the application for business licenses, the socialization of SME development and the imposition of sanctions on SMEs that have been proven to have committed fraud. The Employment Act provides many benefits to SMEs and stimulates economic growth, but the hope is that SMEs have qualified personnel to understand and apply the benefits of the law.